Discovery and Identification of an Endogenous Metabolite of Tramiprosate and Its Prodrug ALZ-801 that Inhibits Beta Amyloid Oligomer Formation in the Human Brain - Hey, John A; Kocis, Petr; Hort, Jakub; Abushakra, Susan; Power, Aidan; Vyhnálek, Martin; Yu, Jeremy Y; Tolar, Martin (CNS drugs, 2018)
BACKGROUND: ALZ-801 is an oral, small-molecule inhibitor of beta amyloid (Aβ) oligomer formation in clinical development for Alzheimer's disease (AD). ALZ-801 is a prodrug of tramiprosate with improved pharmacokinetic properties and gastrointestinal tolerability. During clinical studies, we discovered that the primary metabolite of tramiprosate and its prodrug ALZ-801, 3-sulfopropanoic acid (3-SPA), is an endogenous molecule in the human brain and present in the cerebrospinal fluid (CSF) of patients with AD and other neurodegenerative brain diseases. OBJECTIVE: The objectives of this research were to (1) identify and confirm the presence of 3-SPA in CSF samples from elderly, drug-naïve patients with memory deficits; (2) quantify the levels of 3-SPA in the CSF of patients with AD from tramiprosate phase III North American (NA) trial; (3) evaluate the in vitro anti-Aβ42 oligomer activity of 3-SPA; and (4) characterize the pharmacokinetics and brain-penetration properties of 3-SPA. METHODS: Lumbar CSF samples from 64 drug-naïve patients with cognitive deficits (Mini-Mental State Examination [MMSE] score range 15-30) and six patients with AD treated with tramiprosate 150 mg twice daily in the phase III trial, at week 78, were analyzed. We used liquid chromatography-tandem mass spectrometry to confirm the structural molecular identity of endogenous 3-SPA with a 3-SPA reference standard and ion-mobility spectrometry-mass spectrometry with molecular dynamics to characterize interactions of 3-SPA with Aβ42 monomers, and the resultant conformational alterations. Rat studies using oral (30 mg/kg) and intravenous (10 mg/kg) doses were conducted to characterize the pharmacokinetic properties and brain penetration of 3-SPA. RESULTS: We confirmed the presence of 3-SPA in the CSF of drug-naïve patients with cognitive deficits (mean concentration 11.7 ± 4.3 nM). The mean concentration of 3-SPA in patients with AD treated with tramiprosate was 135 ± 51 nM. In vitro studies revealed a multi-ligand interaction of 3-SPA with monomeric Aβ42 that inhibits the aggregation of Aβ42 into small oligomers. Comparisons of the molecular interactions of tramiprosate and 3-SPA with Aβ42 are also presented. Furthermore, in rat preclinical studies, 3-SPA displayed 100% oral bioavailability and 25% brain penetration, indicating that the metabolite is well absorbed and crosses the blood-brain barrier. CONCLUSIONS: We confirmed the endogenous presence of 3-SPA, the major metabolite of tramiprosate, in the CSF of drug-naïve elderly patients with memory deficits due to AD and a variety of other neurodegenerative disorders. The levels of 3-SPA were up to 12.6-fold greater in patients with AD receiving tramiprosate than in drug-naïve patients. In addition, we showed that 3-SPA has potent anti-Aβ oligomer activity, inhibiting aggregation of Aβ42 into small oligomers with efficacy comparable to that of tramiprosate. 3-SPA displays excellent oral availability and brain penetration in rats, suggesting that the higher CSF concentrations of 3-SPA in the human brain after oral administration of ALZ-801 or tramiprosate (and subsequent conversion to 3-SPA) result from the penetration of the metabolite into the central nervous system. These data suggest that 3-SPA is an endogenous agent with potential activity stabilizing the conformational flexibility of Aβ monomers that, in turn, inhibit Aβ misfolding and formation of soluble toxic Aβ oligomers in humans, thereby preventing the initial pathogenic step in the progression of AD. Clinical improvements observed in patients with AD carrying the ε4 allele of the apolipoprotein E gene in tramiprosate phase III studies may in part be explained by the therapeutic effects of excess levels of the metabolite in the brains of these patients. The potential protective role of 3-SPA in AD pathogenesis, as well as its therapeutic role in AD and other neurodegenerative disorders, warrants further investigation.
Keywords: Animals; způsoby aplikace léků; Female; Valine; Propionates; Amyloid beta-Peptides; Nonlinear Dynamics; Prodrugs; počítačová simulace; kognitivní poruchy; ženské pohlaví; Tandem Mass Spectrometry; lidé; amyloidní beta-protein; Chromatography, Liquid; Mental Status Schedule; prekurzory léčiv; mozek; Cognition Disorders; Taurine; peptidové fragmenty; Computer Simulation; Rats, Sprague-Dawley; chemické modely; taurin; Male; tandemová hmotnostní spektrometrie; potkani Sprague-Dawley; valin; Aged; Brain; Peptide Fragments; Alzheimer Disease; nelineární dynamika; krysa rodu Rattus; Alzheimerova nemoc; záznam o duševním stavu; lidé středního věku; Models, Chemical; senioři; zvířata; mužské pohlaví; Drug Administration Routes; propionáty; Middle Aged; Rats; chromatografie kapalinová; Humans